Unusual cause of fatal anthrax meningitis. (28th March 2014) - Parlak, Emine; Parlak, Mehmet; Atli, Seval Bilgiç
Abstract: We report the case of fatal anthrax meningoencephalitis in the province of Muş located in eastern Anatolia, Turkey. The organism isolated from cerebrospinal fluid was identified as Bacillus anthracis . The patient was treated with crystallized penicillin G (24 MU/day IV) and ciprofloxacin (2 × 400/day IV), but died 5 days after hospitalization. Although it is a rare case, we consider that the patients who have skin, respiratory and neurological systems might also have hemorrhagic meningitis.